The force-sensitive protein Ajuba regulates cell adhesion during epithelial morphogenesis. - Razzell, W.; Bustillo, M.E.; Zallen, J.A. (Journal of Cell Biology, 2018)
The reorganization of cells in response to mechanical forces converts simple epithelial sheets into complex tissues of various shapes and dimensions. Epithelial integrity is maintained throughout tissue remodeling, but the mechanisms that regulate dynamic changes in cell adhesion under tension are not well understood. In Drosophila melanogaster, planar polarized actomyosin forces direct spatially organized cell rearrangements that elongate the body axis. We show that the LIM-domain protein Ajuba is recruited to adherens junctions in a tension-dependent fashion during axis elongation. Ajuba localizes to sites of myosin accumulation at adherens junctions within seconds, and the force-sensitive localization of Ajuba requires its N-terminal domain and two of its three LIM domains. We demonstrate that Ajuba stabilizes adherens junctions in regions of high tension during axis elongation, and that Ajuba activity is required to maintain cell adhesion during cell rearrangement and epithelial closure. These results demonstrate that Ajuba plays an essential role in regulating cell adhesion in response to mechanical forces generated by epithelial morphogenesis.